An Investigation into the contribution of table egg production to household protein consumption in Goromonzi district - Chiuya, Vimbainashe (BUSE, 2019)
This study determined the contribution of table egg production to household protein consumption in Goromonzi District. Data was collected via questionnaires and focus group discussions and analysed using SPSS. The study showed many residents in peri-urban communities were into table egg production projects which contributed immensely to the consumption of protein with over 88% of the respondents agreeing to this claim. Egg consumption was, therefore, a ready alternative for many who could not afford to purchase meat regularly but would still get valuable protein from the product. The study also showed that egg consumption is not only limited to breakfast but also consumed at lunch (33%) and super (52%) as relish to the staple food sadza. Furthermore, the study managed to give recommendations to the relevant stakeholders to rally behind smallholder farmers on egg production in peri-urban communities on how best these projects can be adopted. Keywords: household protein consumption; Nutrition; table eggs;
Keywords: Table egg production; Hosehold protein consumption